1988
DOI: 10.1029/jb093ib07p07955
|View full text |Cite
|
Sign up to set email alerts
|

Slip vectors and fault mechanics in the Makran Accretionary Wedge, southwest Pakistan

Abstract: The Makran is a broadly east–west trending arcuate accretionary wedge currently forming where the oceanic floor of the Gulf of Oman is being subducted north‐northeastward beneath the south Asian margin. Two traverses across the Makran Coast Ranges, extending about 80 km inland from the coastline (which lies about 100 km north of the wedge front), show that the structure of this region is dominated by large back‐rotated south directed thrust faults and associated folds. Related structures include duplexes, faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…This hinders field investigations of emergent examples as well as seismic studies of currently active complexes in submerged fore-arcs. In spite of this, some excellent seismic studies have demonstrated that the frontal regions of accretionary wedges are dominated by imbricate thrusting (Davey et al, 1986;Davis and Hyndman, 1989;Moore et al, 1990;Morgan and Karig, 1995), and this has been confirmed by detailed studies of some well-exposed emergent examples (Moore and Karig, 1980;Wahrhaftig, 1984;Platt et al, 1988;Meneghini andMoore, 2007, Wakabayashi, 2017). The structure of the more deeply buried interiors of accretionary wedges is less well documented, and in particular the processes driving exhumation of these rocks remain controversial.…”
Section: Introductionmentioning
confidence: 97%
“…This hinders field investigations of emergent examples as well as seismic studies of currently active complexes in submerged fore-arcs. In spite of this, some excellent seismic studies have demonstrated that the frontal regions of accretionary wedges are dominated by imbricate thrusting (Davey et al, 1986;Davis and Hyndman, 1989;Moore et al, 1990;Morgan and Karig, 1995), and this has been confirmed by detailed studies of some well-exposed emergent examples (Moore and Karig, 1980;Wahrhaftig, 1984;Platt et al, 1988;Meneghini andMoore, 2007, Wakabayashi, 2017). The structure of the more deeply buried interiors of accretionary wedges is less well documented, and in particular the processes driving exhumation of these rocks remain controversial.…”
Section: Introductionmentioning
confidence: 97%
“…It has been formed by the subduction of the oceanic portion of the Arabian Plate beneath Eurasia and is built up by sediments scraped off the Arabian Plate since early Tertiary (Berberian and King, 1981;Harms et al, 1984;Kopp et al, 2000). Subduction was probably initiated during Palaeocene (Platt et al, 1988) and accretion started during Eocene times (Byrne et al, 1992). The modern Makran accretionary prism has developed since Late Miocene (Platt et al, 1985;Platt et al, 1988), and is still propagating seaward at a rate of ~10 mm yr -1 (White, 1982).…”
Section: Makranmentioning
confidence: 99%
“…Subduction was probably initiated during Palaeocene (Platt et al, 1988) and accretion started during Eocene times (Byrne et al, 1992). The modern Makran accretionary prism has developed since Late Miocene (Platt et al, 1985;Platt et al, 1988), and is still propagating seaward at a rate of ~10 mm yr -1 (White, 1982). Two features make this accretionary wedge unusual: (1) the sediment thickness on top of the oceanic crust is extremely high (at least 6 km); and (2) the dip angle of subduction is extremely low (~5 degrees, Jacob and Quittmeyer, 1979;Byrne et al, 1992;Carbon, 1996).…”
Section: Makranmentioning
confidence: 99%
“…Makran Subduction Zone (MSZ) is distinctive region due to its abnormal behavior of seismicity and structural complexities due to slow rate of subduction. Subduction was probably initiated during Palaeocene time by Platt et al and accretion started during Eocene time [1] and accretion started during Eocene time [2].…”
Section: Introductionmentioning
confidence: 99%